KARAKTERISTIK FITUR-FITUR KEBAHASAAN TOKOH LAKI-LAKI DAN PEREMPUAN DALAM KOMIK DETEKTIF CONAN EDISI 28 - Nugraha, Dana Dwi; Prasetiyo, Anggik Budi (Fakultas Bahasa dan Sastra Indoensia, 2022)
The purpose of this study is to find and describe the form of language features used by male and female characters in comics. The research data is in the form of words that are indicated to contain linguistic features of male and female characters in comics of Detective Conan 28th Edition. The results of this study have five scopes including Empty Adjectives, Hedge, Intensifier, Hypercorrect Grammar, Super Polite Form, Avoidance of Strong Swear Words, Emphatic stress. According data that analyzed with linguistic method of Robin Tolmach Lakoff, women are more dominant than men for beliefs, admiration, and forms of expression. Meanwhile, men are more dominant in the expression of beliefs and doubts.